ZONAL IMPACT ASSESSMENT BASED ON ZONAL COMMUNITY PREFERENCES: AN ALTERNATIVE OF LAND DEVELOPMENT CONTROL IN DEVELOPING COUNTRIES - K. Limapornwanitch; K. Teknomo; K. Hokao (Lowland Technology International, 2004)
Many planners have recently utilized the Development Impact Assessment framework focuses on the site specific level, and mostly concerns only limited types of development impacts. In fact, the city growths are the results of simultaneous developments and their adverse impacts are diverse, such as economic losses and environmental degradations. These become the limitations of impact assessment to manage the actual urbanizations. We have developed a framework of Zonal Impact Assessment (ZIA) to evercome those limitations. Our framework mainly evaluates the generated impacts in each zone rather than an isolated project. The ZIA can analyze the impacts of simultaneous developments in many zones, and many kinds of impacts can be considered. Furthermore, the survey results of public participation were included to identify the sensitive areas for development impact based on the preferences of zonal communities. The Bangkapi case study was elucidated to demontrate the ZIA application concerning traffic impacts of developments. The Impact distributions were evaluated and visualized for planning process. It wa found that ZIA is an alternative tool in balancing between infrastructure demands and urban developments to reach a sustainable community.